(untitled) (Circe de clásicos y modernos, 2026)
In this short paper, I aim to analyze the scholarly literary recreation of selected Virgilian quotations from the Aeneid carried out by the Argentine writer Manuel Mujica Lainez in his novel Bomarzo (1962), a work studied from various disciplinary perspectives, yet rarely through the lens of classical philology, particularly in terms of tradition and recasting. As I will explain, the textual citation of the Roman poet in the novel is not merely a rhetorical appeal to authority, but above all a literary device that allowed the author, after grasping the original meaning and context of the passage, to adapt it to the new setting of his Renaissance epic, thereby reactivating Virgil’s text within another narrative framework: a Virgilian palingraph.